Alpha-1 Acid Glycoprotein Cut-off Value as Diagnostic Biomarker in Hepatocelular Carcinoma with Liver Cirrhosis - Maulana Suryamin; Rino A Gani; Murdani Abdullah; C Martin Rumende (The Indonesian Society for Digestive Endoscopy, 2014)
Background: Hepatocellular carcinoma (HCC) remains a major problem throughout the world, especially in diagnostic and therapeutic management. Previous studies stated that alpha-1 acid glycoprotein (AAG) was a potensial biomarker in diagnostic of HCC. This study assessed the best cut-off value of AAG as a diagnostic biomarker of HCC with liver cirrhosis.Method: This was a cross-sectional, diagnostic study, conducted from January to October 2013 in Cipto Mangunkusumo Hospital. The subjects were HCC with liver cirrhosis patients and as control were liver cirrhosis patients. Abdominal ultrasonography (USG), abdominal 3 phase contrast computerized tomography (CT) scan, and liver biopsy, if necessary, were done. All patients were having AAG examination, then the result was analyzed using receiver operating characteristic (ROC) curve and assessment of some cut-off values was done.Results: There were 25 HCC with liver cirrhosis patients and 37 liver cirrhosis patients as control included in this study. HCC with liver cirrhosis patients were 92% male and 8% were female, over 50 years old (72%). HBV infection was the most common etiology and most of the patients had multiple nodules in the liver (80%). ROC curve showed the area under the curve (AUC) was 81.44%.Conclusion: The best cut-off value of AAG to be aware of HCC with liver cirrhosis was 61 mg/dL and as a diagnostic was 136 mg/dL. Keywords: hepatocelullar carcinoma, alpha-1 acid glycoprotein, cut-off